Tax and public finances: The fundamentals - Isaac Delestre; Helen Miller (Institute for Fiscal Studies (IFS), 2023)
This report highlights 10 key facts about UK tax and public finance policy that will underpin the choices faced by governments in coming decades.
Keywords: 330; Business and investment; Consumption and prices; Government finances and spending; Poverty; inequality and social mobility; Taxes and benefits; Consumer behaviour; Corporate taxes; Distributional effects; Firms; Healthcare; Income taxes; Inequality; Investment; Living standards; NHS; Pay; Productivity; Property taxes; Public finance; Public sector; Tax; Taxes on wealth and spending; VAT; Wealth